Optimization of Social Media as a Means of Promotion and Marketing for MSME Products in Tanjung Duren Utara, West Jakarta - Agtovia Frimayasa; Ibnu Haris Nasution; Yanthy Herawaty Purnama; Rahmat Rahmat (Abdimas Paspama, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy but still face challenges in marketing their products. Social media serves as a viable solution to enhance MSME promotion and market reach at a relatively low cost. This Community Service Program (PKM) aims to enhance the capacity of MSME entrepreneurs in Tanjung Duren Utara in optimizing the use of social media for product marketing. The methods used in this program include training, mentoring, and evaluation of the digital marketing strategies implemented by participants. The results indicate an improvement in participants' understanding and skills in managing social media as an effective marketing tool.